The Effect of Financial Crisis on the Quality of Financial Reporting - Seyed Kazem Ebrahimi (Ph.D) (Shahid Bahonar University of Kerman, 2017)
Managers of companies that are facing financial crisis, have high incentives to use discretionary accruals and earnings because of declining profitability and the resulting stock price decline his bonus, such acts lead to a reduction in earnings quality and reduce the quality of financial information, So the financial crisis has weakened the trust of investors in financial reporting system and the quality of its accounting is of great importance. The purpose of this research is to determine the effect of financial crisis on quality of financial reporting. In this study we use a sample of 90 firms listed in Tehran Stock Exchange during the period 2002 to 2015. The results of multiple regression model and panel data with fixed and random effects, showed that financial crisis has significant negative effect on the earning smoothing, value relevance and conditional conservatism, but it was not found significant correlation between the financial crisis with unconditional conservatism.